Perlindungan pohon induk jernang (Daemonorops spp.) di Mandiangin, Jambi - Revis Asra; Ade Octavia; Lisna Lisna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Jernang rattan is one of the superior products of Jambi Province, besides palm and rubber, unlike most rattan which is used from the stem, but the used of jernang is the red resin. Jernang has the potential to be integrated in rubber plantations, so it is the right solution to improve the economy of rubber farmers in Liam Lestari Village Mandiangin District, Sarolangun District. The difficulty of getting old seeds as a source of seedlings is a major obstacle in jernang cultivation. In Liam Lestari village, one rubber farmer was found who had made clear integration, but the jernang fruit was often stolen, so that no old seeds were used for seedlings. Community Service Activities with a scheme of Regional Superior Product Development Program (PPPUD) is one solution to overcome the difficulties of seedlings in Mandiangin. The service method used is Participatory Rural Apraisal. PPPUD activities involve the Jernang Lestari farmer group. Based on the results of dedication by protecting the parent tree through fencing with bulian wood, it can overcome the problem of theft of jernang fruit.